Half the sky: turning oppression into opportunity for women worldwide - Kristof, Nicholas D. (Vintage Books, 2010)
Two Pulitzer Prize winners issue a call to arms against our era's most pervasive human rights violation: the oppression of women in the developing world. They show that a little help can transform the lives of women and girls abroad and that the key to economic progress lies in unleashing women's potential